2020
DOI: 10.1002/ijfe.2094
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic risk attributes in Malaysia stock markets: Behavioural finance insights

Abstract: This paper proposes a quasi‐rational multi‐factor stock‐pricing determinants model with fundamental (rational) and behavioural (irrational) risk factors that highlight academic and practical merits. Academically, this study provides proofs to the notion of bounded rational and dynamic risk–return relationships. Practically, ways to uncover dynamics risk attributes in equity markets are highlighted. The empirical tests are performed based on a sample of 238 Malaysian firm stock returns with monthly data spannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 113 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, studies on the emerging market are becoming increasingly popular as investors seek diversification opportunities. Various theoretical explanations for stock market linkages have emerged from the growth economies of knowledge on the subject, including the law of one price and theories of stock market movement and stock market interdependence derived from Modern portfolio theory, which all serve to justify stock market linkages [16,17]. Theories underline portfolio diversification in global markets [18][19][20].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…On the other hand, studies on the emerging market are becoming increasingly popular as investors seek diversification opportunities. Various theoretical explanations for stock market linkages have emerged from the growth economies of knowledge on the subject, including the law of one price and theories of stock market movement and stock market interdependence derived from Modern portfolio theory, which all serve to justify stock market linkages [16,17]. Theories underline portfolio diversification in global markets [18][19][20].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In the case of the evolving EdTech market globally, the investor's behavior can be captured using the prospect theory in behavioral finance. Prospect theory conceptualizes the decision-making process of investors when they encounter circumstances that encompass risk, probability and uncertainty (Tuyon and Ahmad, 2021). Investors' decisions to invest their capital are based on their perceptions of the gains and losses involved.…”
Section: The Expected Utility Theorymentioning
confidence: 99%
“…Several empirical studies have shown that investors emotions influenced Malaysian stock returns [2][3][4][5]. The relationship between the returns of Malaysian stocks and investor feelings driven by fear of dangerous infectious diseases has been investigated and provided evidence that the SARS significantly affect the Malaysian stock market behaviour [6].…”
mentioning
confidence: 99%